2018
DOI: 10.1097/qad.0000000000001872
|View full text |Cite
|
Sign up to set email alerts
|

Neurodevelopment of breastfed HIV-exposed uninfected and HIV-unexposed children in South Africa

Abstract: Young HEU children may be at increased risk for cognitive and motor delay despite universal maternal ART and breastfeeding; those born preterm may be particularly vulnerable.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
110
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 81 publications
(119 citation statements)
references
References 44 publications
(57 reference statements)
8
110
1
Order By: Relevance
“…In Botswana, between 2010 and 2012 when only one‐third of mothers received combination ART during pregnancy and <10% of CHEU were breastfed compared to >99% of CHU, there was little evidence of differences in neurodevelopment at 24 months of age (N = 724) . However, in the era of combination maternal ART and breastfeeding in South Africa, CHEU had higher odds of cognitive and motor, although not language, delay at 13 months of age (N = 521) . Our study population and findings are closer to the South African study; however, in using more detailed language assessments for two‐year‐old children, we additionally found differences in vocabulary scores between groups.…”
Section: Discussionsupporting
confidence: 48%
See 1 more Smart Citation
“…In Botswana, between 2010 and 2012 when only one‐third of mothers received combination ART during pregnancy and <10% of CHEU were breastfed compared to >99% of CHU, there was little evidence of differences in neurodevelopment at 24 months of age (N = 724) . However, in the era of combination maternal ART and breastfeeding in South Africa, CHEU had higher odds of cognitive and motor, although not language, delay at 13 months of age (N = 521) . Our study population and findings are closer to the South African study; however, in using more detailed language assessments for two‐year‐old children, we additionally found differences in vocabulary scores between groups.…”
Section: Discussionsupporting
confidence: 48%
“…Recent studies from the ART era, published since this systematic review, have generally found poorer neurodevelopment amongst CHEU compared to CHU. At 12 months of age, a study from South Africa found increased odds of cognitive and motor delay . At two years of age, a study from Botswana showed expressive language delay and a study from South Africa found receptive and expressive language delay .…”
Section: Introductionmentioning
confidence: 99%
“…Studies from various settings have reported that HIV exposed, uninfected children (HEU) have poorer health outcomes than HIV unexposed uninfected children (HUU) [19][20][21][22][23]. Thus, HEU children seem to be disadvantaged with respect to birth outcomes such as preterm birth, linear growth, metabolism, adaptive and innate immune systems; and increased infectious morbidity [24].…”
Section: Introductionmentioning
confidence: 99%
“…Previous reviews have reported some delays in cognitive, language or motor development, [47,49,50] although to a lesser extent than in CLHIV and mainly in low-resource settings. [47] A recent study from SA found motor and cognitive delay, particularly associated with preterm birth, [51] and a study from Zambia reported a later impact on school performance. [52] However, other studies in Botswana [53] and SA [54] have not found substantial differences when compared with HIV-unexposed children, although some language impairment was demonstrated, which has also been seen in high-income settings.…”
Section: Early Neurodevelopmentmentioning
confidence: 99%